1-Shot hot stamping of ultra-high strength steel parts consisting of resistance heating, forming, shearing and die quenching. (February 2015) - Mori, Ken-ichiro; Maeno, Tomoyoshi; Yamada, Hiroaki; Matsumoto, Hayato
Abstract: A 1-shot hot stamping process consisting of resistance heating, forming, shearing and die quenching was developed to produce small- and medium-size ultra-high strength steel parts. A rectangular sheet was resistance-heated to obtain a uniform distribution of temperature, and just after the end of heating, a sequence of forming, shearing and die quenching was performed by one shot to prevent the drop in temperature. An ultra-high strength steel spur gear having a hardness of 540 HV2 was produced by 1-shot hot stamping composed of heating, blanking and die quenching. The rollover was improved by partial compression of the blanked gear. An ultra-high strength stainless steel part having a hardness of 580 HV2 was produced by 1-shot hot stamping consisting of the heating, bending, shearing and die quenching, and no springback and quenching distortion of the produced part were observed by holding at the bottom dead centre of the press. An operation for thickening the edge of the punched hole was included in 1-shot hot stamping to improve the strength of a product.